Decision Initiation, Decision Implementation, and the Allocation of Decision Rights - Randolph Sloof; Ferdinand von Siemens (Center for Economic Studies and ifo Institute (CESifo), 2015)
Organizations must not only take the right decisions, they must also ensure that these decisions are effectively implemented. Fama & Jensen (1983) argue that the same members of many organization are often responsible for both decision initiation and implementation. If these have social preferences, they might thus sabotage both project choices and implementation to express their discontent with the allocation of decision rights. How decisions come about also affects implementation if workers have reciprocal fairness concerns. Our experimental evidence demonstrates that the possibility to sabotage implementation leads to more delegation, but only if workers have high costs of obstructing informed decisions. We further find that the allocation of authority as such affects implementation.
Keywords: C91; D23; D86; L20; 330; delegation; implementation; procedural preferences; reciprocity